Associations between depressive symptoms with perceived future time and opportunities: tests of unique prediction and moderation. (2nd January 2022) - Hill, Patrick L.; Allemand, Mathias
Abstract: Objectives: Having a broadened perspective on one's future has been associated with better affective well-being, including reduced reports of depressive symptoms. However, research is limited regarding which aspect of future time perspective is associated with depressive symptoms, and whether these findings are consistent across individuals. Methods: The current study employed data from a nationally representative sample of Swiss adults ( n  = 1774; mean age: 49.90 years; 51.8% female). Participants completed measures of future time perspective – both perceptions of future time and future opportunities – and depressive symptoms, in addition to reporting on their age, sex, health, and socioeconomic status (the moderators of interest). Results: Perceived future time and future opportunities were uniquely predictive of depressive symptoms, even when controlling for chronological age and other covariates, though future opportunities held a stronger association with depressive symptoms. Limited evidence was found for moderation, though opportunities may matter more for predicting depressive symptoms among adults in worse health and those with fewer resources. Discussion: Future time perspective appears moderately associated with depressive symptoms in adulthood, and researchers need to consider multiple aspects of future time perspective rather than as a unitary construct.